The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00586-019-06155-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction mammoplasty and back pain: a systematic review and meta-analysis

Abstract: Purpose There is anecdotal evidence that many patients who undergo reduction mammoplasty (RM) procedures, to relieve symptoms of large breasts, also report improvement in existing back pain. Given how important back pain is as a healthcare burden, the literature which explores the relationship between RM and back pain is sparse. Thus, we aimed to appraise whether such a correlation exists, through systematic review and meta-analysis. Method Adhering to PRISMA methodology, we used the OVID engine to search the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The combination of removing breast fat, glandular tissue, and skin allows the surgeon to decrease breast weight and restructure the breast to a more pleasing appearance 1 . The indications for reduction mammaplasty include aesthetic concerns and therapeutic reasons such as decrease of breast weight for treatment of complaints of breast and skeletal pain (mainly back and neck pain), 2,3 ptosis, intertriginous skin disorders of the inter‐ or sub‐mammary fold, and psychological disorders 4,5 . When performed for therapeutic reasons, bilateral reduction mammaplasty is one of the few plastic surgeries that health insurance providers in many countries will recognise and routinely pay for 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…The combination of removing breast fat, glandular tissue, and skin allows the surgeon to decrease breast weight and restructure the breast to a more pleasing appearance 1 . The indications for reduction mammaplasty include aesthetic concerns and therapeutic reasons such as decrease of breast weight for treatment of complaints of breast and skeletal pain (mainly back and neck pain), 2,3 ptosis, intertriginous skin disorders of the inter‐ or sub‐mammary fold, and psychological disorders 4,5 . When performed for therapeutic reasons, bilateral reduction mammaplasty is one of the few plastic surgeries that health insurance providers in many countries will recognise and routinely pay for 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown significant alleviation of pain after the reduction of mammoplasty [ 17 ]. The obtained results also showed a significant reduction in the neck, shoulder, and back pain after operation in patients with pre-op BMI>30.…”
Section: Discussionmentioning
confidence: 99%
“…The findings resulted from this study consistent with previous reviews of this subject and are supported by other publications with other outcomes that are not mentioned in this review. Mian et al 25 have also found that breast reduction reduces the prevalence of back pain in women with large breasts. That is because breast hypertrophy deranges the spinal angles relating to thoracic kyphosis, lumbar lordosis, and the correct alignment of the sacrum, 40,41 and breast tissue resection could improve this pathological status quo.…”
Section: Hadsmentioning
confidence: 95%
“…Many researchers have studied the relationship between operation and postoperative quality of life. Mian et al 25 have reported that reduction mammaplasty reduces the prevalence of back pain in patients with breast hypertrophy. Some authors have concluded that operation has a positive impact on women's sexual function, sexual quality of life, and sexual well-being 11,26 .…”
mentioning
confidence: 99%